Ab initio computational study: Adsorption of CO molecule on various base metal oxide surfaces. Issue 1 (October 2020) - Kurnia, I; Siahaan, P; Suseno, A
Abstract: The use of some base metal oxide already widely studied for having beneficial properties in CO oxidation catalytic system. The properties of these base metals such as lower working temperature, high CO affinity, and economically cheaper would be beneficial for this solid system catalyst. The study of various base metal oxides shown these kinds of characteristics, but there still a few analyses of comparison among the various base oxide metals used as the support system for the oxidation reaction catalytic system. This study would give a comparison in the difference of the adsorption energy of various base oxide metals. This adsorption energy is one factor that promoting the activity of the catalytic system due to its affinity to the reactant on their surfaces. The DFT ab initio calculation for this comparison shows that NiO is the base metal oxide that having the highest CO adsorption energy. This oxide could be a potential support system combined with potential solid oxidative catalytic system.